Variation in susceptibility of insects associated with Kansas farm-stored grain to insecticides recommended for empty bin treatments - Sehgal, Blossom (My University, 2013)
Producers apply insecticides to empty bins to kill insects prior to storing newly-harvested grain. We evaluated time-dependent immediate knockdown (KD) and 7-day mortality responses of adults of 16 strains of the red flour beetle, 7 strains of the sawtoothed grain beetle and 2 strains of the lesser grain borer collected from Kansas farms exposed on concrete surfaces to β-cyfluthrin, at low (0.086 mg(AI)/m2) and high (0.172 mg(AI)/ m2) rates, and chlorpyrifos-methyl plus deltamethrin (0.573 mg(AI)/m2). Similar species reared since 1999 served as standard laboratory strains. The minimum time for KD and mortality of laboratory strains was established through time-response studies. Time for 100% KD and mortality was selected for each insecticide-species combination for testing against field strains. Mortality of all species against the two insecticides was lower than KD, suggesting recovery when placed on food. Nonlinear or linear models fitted to KD and mortality data showed significant differences among species and insecticides. Only one red flour beetle strain showed reduced susceptibility to the two insecticides compared to the laboratory strain. Both field strains of lesser grain borers were less susceptible than the laboratory strain to chlorpyrifos-methyl plus deltamethrin but not to β-cyfluthrin. In sawtoothed grain beetle, one strain was significantly less susceptible to chlorpyrifos-methyl plus deltamethrin than the laboratory strain, and two field strains were significantly less susceptible to β-cyfluthrin. Reduced susceptibility in field strains could be due to development of resistance. These findings can be used to make recommendations to producers for improved stored-grain insect management.
Keywords: chlorpyrifos-methyl + deltamethrin; β-cyfluthrin; saw-toothed grain beetle; lesser grain borer; red flour beetle; field strains